From the closet to the city: LGBTQIA+ memory, identity, and spatial shifts in urban and audiovisual contexts (PerCursos, 2026)
This article reflects on the relationships between memory, LGBTQIA+ identity, and urban spatiality through an autoethnographic approach situated in the city of Belém, Pará, Brazil. Drawing on personal experiences as a cisgender gay man, the study mobilizes memory fragments to analyze transformations in how LGBTQIA+ individuals have occupied urban space since 2012, highlighting a shift from affective practices once confined to marginal and less visible spaces toward more public contexts. In dialogue with Candau (2021), Castells (2010), and Chang (2016), the article also examines how these changes intersect with transformations in audiovisual productions, which have increasingly portrayed LGBTQIA+ identities in less stigmatized and more diverse ways. It argues that such movements, although shaped by market interests, contribute to the strengthening of collective identities and to the expansion of possibilities for existence in social space. Thus, the article demonstrates how individual memory, collective experience, and cultural representations intertwine in the construction of new forms of visibility and belonging.
Keywords: memories; LGBTQIA+ identities; autoethnography; city; audiovisual